Investigation of tadalafil molecular arrangement in solid dispersions using inverse gas chromatography and Raman mapping - Školáková, Tereza; Smržová, Dominika; Pekárek, Tomáš; Lhotka, Miloslav; Školáková, Andrea; Klimša, Vojtěch; Kadeřábková, Alena; Zámostný, Petr (International journal of pharmaceutics, 2022)
The aim of this study was to investigate the molecular structures of tadalafil solid dispersions prepared by different techniques and further to relate them to surface free energy information indicating the final amorphousness of the product. Thus, we tried to complement the existing knowledge of solid dispersion formation. Poorly water-soluble tadalafil was combined with different polymers, i.e. Kollidon® 12 PF, Kollidon® VA 64 and Soluplus®, to form model systems. To assess the extent of drug-polymer miscibility, we studied model solid dispersion surface energy using inverse gas chromatography and phase micro-structure using confocal Raman microscopy. The selection of the preparation method was found to play a crucial role in the molecular arrangement of the incorporated drug and the polymer in resulting solid dispersion. Our results showed that a lower surface free energy indicated the formation of a more homogeneous solid dispersion. Conversely, a higher surface free energy corresponded to the heterogeneous systems containing tadalafil amorphous clusters that were captured by Raman mapping. Thus, we successfully introduced a novel evaluation approach of the drug molecular arrangement in solid dispersions that is especially useful for examining the miscibility of the components when the conventional characterizing techniques are inconclusive or yield variable results.
Keywords: polymery; Polymers; chromatografie plynová; povidon; tadalafil; rozpustnost; Povidone; Tadalafil; Chromatography, Gas; Solubility